Causal modeling in impulsive systems: A new rigorous non-standard analysis approach. (August 2017) - Hyun, Nak-seung P.; Verriest, Erik I.
Abstract: A new approach for modeling nonlinear impulsive system is suggested based on nonstandard analysis. Basic properties of the hyperreals in nonstandard analysis are revisited. Depending on the convergence rate of infinitesimals in hyperreals, a new extended real space is proposed, which extends the one dimensional real line to a countably infinite dimensional extended real space. Generalized functions are defined via a sequential approach on the extended space, which yields a class of Heaviside functions and singular functions. By using the extended functions, a causal way for characterizing jumps in discontinuous system follows. We illustrate the usefulness of the theoretical development by analyzing three simple cases of impulsive affine system: (1) scalar case, (2) multi-dimensional case, and (3) one dimensional horizontal bouncing ball. The results suggest not only the existence of such infinitesimal models within the jump but also how to detour the equilibrium point while connecting the discontinuous state at the impact.